Odpowiedzi

  • Użytkownik Zadane
2010-02-15T20:55:50+01:00
A) abc-(abc-(-xyz-(xyz-abc)))=abc-(abc-(-xyz-xyz+abc))=abc-(abc+xyz+xyz-abc)= abc-abc-xyz-xyz+abc=abc-2xyz

b) s²t-(st²-(s²t-(st²-s²t)))=s²t-(st²-(s²t-st²+s²t))=s²t-(st²-s²t+st²-s²t)=s²t-st²+s²t-st²+s²t=-2st²

c)x²yz-(xy²z-(xyz²-(x²yz-xy²z)))=x²yz-(xy²z-(xyz²-x²yz+xy²z))=x²yz-(xy²z+xyz²-x²yz+xy²z)=x²yz-xy²z+xyz²-x²yz+xy²z=xyz²
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-15T20:57:20+01:00
A) abc-(abc-(-xyz-(xyz-abc)))=abc-(abc-(xyz-xyz+abc))=abc-xyz+xyz-abc=0
b) s²t-(st²-(s²t-(st²-s²t)))=s²t-(st²-(s²t-st²+s²t))=s²t-(st²-s²t+st²-s²t)=s²t-st²+s²t-st²+s²t=3s²t-2st²
c) x²yz-(xy²z-(xyz²-(x²yz-xy²z)))=x²yz-(xy²z-(xyz²-x²yz+xy²z))=x²yz-(xy²z-xyz²+x²yz-xy²z)= x²yz-xy²z+xyz²-x²yz+xy²z=xyz²